PERFORMANCE OF BOOM CYLINDER REPAIR MECHANISM AND AUTO LUBRICATION SYSTEM OF EX 2500 HITACHI EXCAVATOR - Sianturi, Maranata P.; Sihombing, Rolando; Sembiring, Jesayas (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
Excavators is one of the heavy equipment used to do transport, excavation, loading work that is operated using hydraulic energy. Excavator construction consists of three main parts, which consist of undercarriage, upper structure, and front attachment. During operation, one of the front attachment parts that has the highest performance is the boom cylinder actuator because it carries the entire load of the front attachment activity. The continuous work of the hydraulic boom cylinder will definitely suffer damage that cannot be avoided and can interfere with the performance of the unit. The damage is in the form of external leaks, internal leaks, scratches, and wear. This research aims to identify the types of damage, causal factors, and impacts caused by boom cylinder damage, explain the boom cylinder maintenance system and process, identify bends in the cylinder rod, and provide a reference price for repairing the Hitachi excavator boom cylinder. The methods used in this research are literature study, observation, and interviews. The results indicate that damage can be minimized by performing scheduled maintenance, such as selecting and replacing the right hydraulic oil and grease, cleaning the hydraulic oil cooler every 500 hours, replacing the oil filter every 250 hours according to the maintenance schedule, performing the inspection process during daily checks, operating the unit in the right way, avoiding modifications that can cause overloading, and performing oil analysis every 250 hours to ensure high availability of the unit as planned.